# math

posted by .

Solve using the substitution method: 7x+2y=-37 and -5x+y=44 what are the solutions?

• math -

The second equation tells you that y = 44 + 5x.

Substitute 44 + 5x in place of y in the first equation. You will have to double it, because 2y appears in that equation. Then solve the resulting equation for x.

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### math

solve using the substitution method....(solutions must be in ordered pairs form) 9m+n=24 m-8n=27
3. ### Algebra

Solve using the substitution method. If the system has no solution or an infinite number of solutions, state this. -x + 6y = 54 3x + y = 9
4. ### math

Solve using the substitution method. If the system has no solution or an infinite number of solutions, state this. -2x + 0y = -14 x + 11y = 18
5. ### math

Solve using the substitution method. Show your work. If the system has no solution or an infinite number of solutions, state this. 8y + 2x = 48 2x = 4y – 12
6. ### Algebra

Solve using the substitution method. Show your work. If the system has no solution or an infinite number of solutions, state this. 4x + 4y = -36 4x + 4y = 12
7. ### algebra

Solve using the substitution method. Show your work. If the system has no solution or an infinite number of solutions, state this. 4x + 4y = -36 4x + 4y = 12
8. ### algebra

Solve using the substitution method. State if there are infinite solutions or no solution. 5x + 8y = -4 x= 2 - 3y
9. ### Algebra 1

bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were going …
10. ### Math

17) solve this linear system using the method of substitution. 2y-x=-10 y= -3/2x-1 20) simplify then solve by substitution 2(x-4)+y=6 3x-2(y-3)=13 just need help with these 2.

More Similar Questions